Lipid-lowering Efficacy of Plant Proteins and Their Application Potential - Yue WANG; Chunhua GUAN; Hong BI; Fengyating WU; Yanqin SHEN; Liang TAO; Yang TIAN (Shipin gongye ke-ji)
In recent years, there has been a gradual increase in the prevalence of obesity, hyperlipidaemia, coronary atherosclerosis, non-alcoholic fatty liver disease, and other conditions attributed to shifts in dietary patterns. These chronic ailments resulting from disruptions in lipid metabolism present a significant risk to human health and longevity. Plant protein serves as a high-quality raw material for food production, offering sustenance for daily functioning along with a range of processing attributes and nutritional benefits. Numerous research studies have demonstrated the pivotal role of plant proteins in modulating lipid metabolism. To consolidate the evidence on the lipid-lowering impacts of dietary plant proteins both in vivo and in vitro, summarizes the effects of amino acid composition of glycine, arginine, leucine and other amino acids in proteins on the lipid-lowering effects, discusses their lipid-lowering mechanisms by several pathways, such as adsorption of bile acid and cholesterol in the gut tract, enhancement/inhibition of rate-limiting enzymes in the processes of cholesterol synthesis, fatty acid oxidation, and the conversion of cholesterol to bile acids, modulation of the pathways related to PPAR signaling, cholesterol absorption and lipid synthesis gene expression, and improves the composition of gut microorganisms and metabolites to explore its lipid-lowering mechanism. Furthermore, it assesses the future trajectory and application possibilities of plant proteins, aiming to offer insights for further research on the regulation of lipid metabolism by plant proteins and to advance their utilization in research and practice.